Case Report: Hypothyroidism Misdiagnosed as Fulminant Myocarditis in a Child - Zhang, Nanjun; Shao, Shuran; Yan, Yu; Hua, Yimin; Zhou, Kaiyu; Wang, Chuan (Frontiers in Cardiovascular Medicine, 2021)
Background: Hypothyroidism can lead to bradycardia, reduced cardiac output, cardiac enlargement, and abnormal electrocardiogram. However, hemodynamic instability and malignant arrhythmias due to hypothyroidism is rarely reported in children. Patient Findings: We report the case of a child with third-degree atrioventricular block, cardiogenic shock, and Adams Stokes Syndrome, who was initially misdiagnosed with fulminant myocarditis and was later found to have hypothyroidism during treatment. Summary: The child's condition did not improve after the administration of gamma globulin, methylprednisolone, and isoproterenol. Even after the placement of temporary pacemakers, the therapeutic effect was still not ideal. Upon reviewing the medical history, the child's condition improved rapidly after levothyroxine supplementation. Conclusions: Hypothyroidism is a common disease, but secondary severe cardiovascular lesions are particularly rare in children. Therefore, the delay in diagnosis can lead to serious cardiovascular manifestations. When pediatric patients develop severe AVB and bradycardia, hypothyroidism should be considered as a possible cause.